(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
The article has been subjected to peer review, and has been prepared in connection with the appeal of the Representation of the Russian Orthodox Church in Strasbourg SUMMARY: 1. Problem description - 2. State of Russian Legislation regulating of the legal status of the child extracted alive as a result of abortion - 3. Legal basis for the recognition of human dignity and the right to life of the child extracted alive as a result of abortion - 4. Legal guarantees of recognition of the right to life and human dignity of the child extracted alive as a result of abortion and emergency medical care in foreign legislation - 5. Conclusions.